Gas production from hydrates by CH4-CO2/H2 replacement. (15th February 2017) - Wang, Xiao-Hui; Sun, Yi-Fei; Wang, Yun-Fei; Li, Nan; Sun, Chang-Yu; Chen, Guang-Jin; Liu, Bei; Yang, Lan-Ying
Graphical abstract: Highlights: NGH production from methane steam reforming and CO2 /H2 replacement was proposed. H2 is to decrease the partial pressure of methane and break methane hydrate stability. Higher H2 ratio in feed gas results in higher accumulative gas production ratio but lower CO2 SR. Gas replacement by CO2 /H2 mixture improves gas production ratio and rate. Abstract: A novel natural gas hydrate production method combined with methane steam reforming and CO2 /H2 replacement was proposed to improve the replacement effect and reduce the cost of later gas separation, in which the role of H2 is to decrease the partial pressure of methane in gas phase and help to break the methane hydrate stability. After preparing representative hydrate sediment samples, we conducted a series of experiments to study the characteristics of gas production by the CH4 -CO2 /H2 replacement method. For the composition of CO2 and H2 in the feed gas, an increase in the mole fraction of H2 would result in a higher accumulative gas production ratio during the gas sweep and replacement stages but decrease the CO2 sequestration ratio, which refers to the amount of CO2 captured by the hydrate versus the gross CO2 injected into the hydrate layer. On the contrary, an increase in the mole fraction of CO2 in the feed gas would have a higher CO2 sequestration ratio, but would sacrifice both the gas production rate and the accumulative methane production ratio. Notably, when the mole fraction of the CO2 ranges from 55% to 72%, the amount of CO2 trapped into hydrate phase is close to the amount of methane dissociated from hydrate. Although the accumulative gas production ratio is not the highest in this range, it can meet the dual function of CO2 replacement.